Boosting CO2 electroreduction on a Zn electrode via concurrent surface reconstruction and interfacial surfactant modification. Issue 3 (4th January 2023) - Pan, Hui; Wang, Fang; She, Shixiong; Zhang, Zhengguo; Min, Shixiong
Abstract : Benefitting from the increased number of highly active sites and the formation of a favorable CTAB-modified electrode/electrode interface, the resulting OD-Zn-CTAB electrode exhibits superior activity and selectivity for CO2 electroreduction to CO. Abstract : Herein, we report an effective strategy for improving the electrocatalytic CO2 reduction reaction (CO2 RR) performance of a Zn foil electrode via concurrent surface reconstruction and interfacial surfactant modification. The oxide-derived and CTAB-modified Zn electrode (OD-Zn-CTAB) prepared by electrochemically reducing the air-annealed Zn foil electrode in the presence of CTAB exhibits high electrocatalytic activity and selectivity for CO production with a CO partial current density ( j CO ) of 8.2 mA cm −2 and a CO faradaic efficiency (FECO ) of 90% at −1.0 V vs . the reversible hydrogen electrode (RHE), greatly outperforming the pristine Zn foil (FECO = 32.0%; j CO = 0.5 mA cm −2 ) and OD-Zn (FECO = 77.6%; j CO = 5.0 mA cm −2 ) obtained by electroreduction of annealed Zn. The greatly enhanced CO2 RR performance of OD-Zn-CTAB can be attributed to the increased number of active sites originating from the surface reconstruction and the formation of a favorable CTAB-modified electrode/electrolyte ( E / E ) interface that can efficiently adsorb and activate CO2 while inhibiting the competitive H2 evolution reaction.